Endocrine disruptors and pregnancy: Knowledge, attitudes and practice of perinatal health professionals. A French multicentre survey. (September 2020) - Marguillier, Elodie; Beranger, Remi; Garlantezec, Ronan; Levêque, Jean; Lassel, Linda; Rousseau, Chloe; Lavoue, Vincent; Le Lous, Maela
Abstract: Introduction: Endocrine disruptors (ED) such as phthalates or bisphenol A are ubiquitous and pregnant women and children are particularly vulnerable. Perinatal health professionals are well-placed to inform pregnant women about the risks. We set out to evaluate perinatal health professionals' knowledge of ED and the information they give during pregnancy. Material and Methods: We invited midwives, obstetrician-gynecologists (OB/GYN), general practitioners (GP), and general medicine and OB/GYN residents to respond to a short Google survey between August and November 2018 by email using perinatal network. Results: Out of 4100 questionnaires sent, 1650 completed questionnaires were returned and analyzed. The participation rate was 41 % with the following distribution: midwives (n = 1215, 74 %), OB/GYN residents (n = 102, 6 %), OB/GYNs (n = 129, 8 %), GPs and residents in general medicine (n = 204, 12 %), in private and public hospitals in France. Only 181 of the respondents thought they were well-informed about ED including 160 midwives (11 %). Most of the responding professionals reported not to give any information during pregnancy (n = 946, 57.3 %). Midwives (n = 452, 37.2 %), people >50 years (n = 104, 41.6 %) and people working in private structures (n = 451, 34.9 %) were the most likely to give information, mainly orally. Overall, 346 (74.2 %) of the respondents considered that information about health risks of endocrine disruptors was important and most of them wished they were better informed (n = 1532, 92.9 %). Conclusion: Our study suggests that perinatal health professionals do not have enough medical information, training or tools to communicate about the risks associated with ED to pregnant women and consequently cannot educate them. Research is needed to further explore the risks and support prevention of environmental exposure for pregnant women.